2012
DOI: 10.1248/bpb.b12-00052
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Neurotransmitter Modulation System on Adrenergic Nerves of Caudal Artery in Type 2 Diabetic Goto–Kakizaki Rats

Abstract: The Goto-Kakizaki (GK) rat is a non-obese and spontaneous model of mild Type 2 diabetes mellitus. In the present study, we compared the regulatory mechanisms of endogenous norepinephrine (NE) release from sympathetic nerves of caudal arteries of 12-week-old GK rats and age-matched normal Wistar rats. Electrical stimulation (ES) evoked significant NE release from caudal arteries of Wistar and GK rats. The amounts of NE released by ES were almost equal in Wistar and GK rats, although the NE content in caudal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…However, we observed that the combination of FL and α1AR blocker increased HR. It is also well established that baroreceptors are stimulated by a decrease in vascular tone and subsequent increase in HR [44,45]. Our data suggested that inhibition of α1AR provoked a reduction in vascular tone and activated baroreceptors, thereby increasing HR.…”
Section: Discussionsupporting
confidence: 75%
“…However, we observed that the combination of FL and α1AR blocker increased HR. It is also well established that baroreceptors are stimulated by a decrease in vascular tone and subsequent increase in HR [44,45]. Our data suggested that inhibition of α1AR provoked a reduction in vascular tone and activated baroreceptors, thereby increasing HR.…”
Section: Discussionsupporting
confidence: 75%
“…Downregulated α 2 -adrenoceptor activity thus leads to increased release of endogenous NA, when nerves are stimulated by NA, but not by PE or ISO. Such an effect has been demonstrated in caudal arteries of the Goto-Kakizaki rat which is a widely used rat model of T2DM [38]. Thus, pre-synaptic impairment of the α 2 -adrenoceptor function may play a role in vascular pathology in T2DM, and the results obtained in the present study display patterns which could explain this pathological effect.…”
Section: Discussionsupporting
confidence: 67%